Determining the optimal dose of tenecteplase before endovascular therapy for ischemic stroke (EXTEND-IA TNK Part 2): A multicenter, randomized, controlled study. Issue 5 (July 2020) - Campbell, Bruce CV; Mitchell, Peter J; Churilov, Leonid; Yassi, Nawaf; Kleinig, Timothy J; Yan, Bernard; Thijs, Vincent; Desmond, Patricia M; Parsons, Mark W; Donnan, Geoffrey A; Davis, Stephen M
Background and hypothesis: Intravenous thrombolysis with tenecteplase is more effective than alteplase in achieving substantial reperfusion at initial angiographic assessment and improves functional outcome. However, the optimal dose of tenecteplase remains uncertain. We hypothesized that 0.40 mg/kg tenecteplase is superior to 0.25 mg/kg tenecteplase in achieving reperfusion at initial angiogram, when administered within 4.5 h of ischemic stroke onset, in patients planned to undergo endovascular therapy. Study design: EXTEND-IA TNK part 2 is an investigator-initiated, phase II, multicenter, prospective, randomized, open-label, blinded-endpoint (PROBE) study. Eligibility requires a diagnosis of ischemic stroke within 4.5 h of stroke onset, pre-stroke modified Rankin Scale (mRS)≤3 (no upper age limit), absence of contraindications to intravenous thrombolysis, and large vessel occlusion (internal carotid, basilar, or middle cerebral artery) on multimodal CT. Patients are randomized to IV tenecteplase at either 0.40 mg/kg (max 40 mg) or 0.25 mg/kg (max 25 mg) prior to thrombectomy. Study outcomes: The primary outcome measure is reperfusion on the initial catheter angiogram, assessed as modified Treatment In Cerebral Infarction (mTICI) 2b/3, or the absence of retrievable intracranial thrombus. Secondary outcomes include mRS at day 90 and early neurological improvement (reduction in National Institutes of Health Stroke Scale (NIHSS) by ≥8 points or reaching 0–1) at day 3. Safety outcomes are death and symptomatic intracerebral hemorrhage. Trial registration: ClinicalTrials.gov NCT03340493